Using optogenetics to dissect rod inputs to OFF ganglion cells in the mouse retina - Sladek, Asia L.; Thoreson, Wallace B. (Frontiers in Ophthalmology, 2023)
Light responses of rod photoreceptor cells traverse the retina through three pathways. The primary pathway involves synapses from rods to ON-type rod bipolar cells with OFF signals reaching retinal ganglion cells (RGCs) via sign-inverting glycinergic synapses. Secondly, rod signals can enter cones through gap junctions. Finally, rods can synapse directly onto cone OFF bipolar cells. To analyze these pathways, we obtained whole cell recordings from OFF-type  RGCs in mouse retinas while expressing channelrhodopsin-2 in rods and/or cones. Optogenetic stimulation of rods or cones evoked large fast currents in OFF RGCs. Blocking the primary rod pathway with L-AP4 and/or strychnine reduced rod-driven optogenetic currents in OFF RGCs by ~1/3. Blocking kainate receptors of OFF cone bipolar cells suppressed both rod- and cone-driven optogenetic currents in OFF RGCs. Inhibiting gap junctions between rods and cones with mecloflenamic acid or quinpirole reduced rod-driven responses in OFF RGCs. Eliminating the exocytotic Ca2+ sensor, synaptotagmin 1 (Syt1), from cones abolished cone-driven optogenetic responses in RGCs. Rod-driven currents were not significantly reduced after isolating the secondary pathway by eliminating Syt1 and synaptotagmin 7 (Syt7) to block synaptic release from rods. Eliminating Syt1 from both rods and cones abolished responses to optogenetic stimulation. In Cx36 KO retinas lacking rod-cone gap junctions, optogenetic activation of rods evoked small and slow responses in most OFF RGCs suggesting rod signals reached them through an indirect pathway. Two OFF cells showed faster responses consistent with more direct input from cone OFF bipolar cells. These data show that the secondary rod pathway supports robust inputs into OFF  RGCs and suggests the tertiary pathway recruits both direct and indirect inputs.